2021
DOI: 10.1093/rheumatology/keab190
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of systemic sclerosis globally: a comprehensive systematic review and meta-analysis

Abstract: Objectives We aimed to conduct a systematic review and meta-analysis on the incidence and prevalence of SSc covering the entire literature. Methods This study followed the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement of 2009. We conducted a systematic search in MEDLINE, Web Of Science, and EMBASE to identify articles reporting incidence and/or prevalence of SSc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 76 publications
0
64
0
Order By: Relevance
“…A recent meta-analysis showed that the overall pooled prevalence of SSc globally was 17.6 per 100,000, and the overall pooled incidence rate of SSc was 1.4 per 100,000 person-years. 15 SSc prevalence is higher in the United States and Australia (25 and 24 per 100,000, respectively) than in Europe (15 per 100,000) and Asia (6.8 per 100,000). 15 The incidence rate of SSc is also higher in the United States compared to Asia (1.5-2.0 vs 0.9 per 100,000 person-years).…”
Section: Incidence and Prevalencementioning
confidence: 87%
“…A recent meta-analysis showed that the overall pooled prevalence of SSc globally was 17.6 per 100,000, and the overall pooled incidence rate of SSc was 1.4 per 100,000 person-years. 15 SSc prevalence is higher in the United States and Australia (25 and 24 per 100,000, respectively) than in Europe (15 per 100,000) and Asia (6.8 per 100,000). 15 The incidence rate of SSc is also higher in the United States compared to Asia (1.5-2.0 vs 0.9 per 100,000 person-years).…”
Section: Incidence and Prevalencementioning
confidence: 87%
“…A first explanation of this observed variability could be the existence of significant differences in the design and methods in different studies, concerning both case identification (data sources and case ascertainment) and definition [76][77][78][79]. In particular, although sometimes used also for prevalence and incidence evaluation, 1980 classification criteria suffered from poor sensitivity for early SSc and lcSSc, and were therefore not suitable to this task, inducing other groups [80,81] to use also the classification criteria early SSc proposed by LeRoy and Medsger in 2001 [47].…”
Section: Design and Methodology Of The Studiesmentioning
confidence: 99%
“…Geographical Variability A third reason for the variability in the observed incidence and prevalence could be related to geographical differences in SSc distribution that might also contribute to the variation of demographic parameters. Information on this issue from some large areas of the world (e.g., Africa and South America) is scanty [77]. The disease is more common in North America or Australia than in East Asia [77,79].…”
Section: Timeframe Of the Studiesmentioning
confidence: 99%
“…Systemic sclerosis (SSc) is characterized by microvascular damage and generalized fibrosis in the skin and visceral organs. 1 , 2 , 3 This is a rare disease, with an estimated global prevalence of 3–24 per 100,000. 4 The pooled prevalence estimate in Asia is 6.8 per 100,000.…”
Section: Introductionmentioning
confidence: 99%
“…4 The pooled prevalence estimate in Asia is 6.8 per 100,000. 3 Lung fibrosis occurs in approximately 80% of patients with SSc; 25%-30% develop progressive interstitial lung disease (ILD), 2 which is a leading cause of morbidity and mortality, with a 10-year mortality of up to 40%. 1 Early diagnosis of SSc-ILD is crucial to initiate treatment and to prevent disease progression.…”
Section: Introductionmentioning
confidence: 99%